Application of solid phase technique in the synthesis of certain heterocycles of expected pharmaceutical interest - Mohamed Tawfik Mohamed Nemr; Hanan Mohamed Refaat; Mohamed Mohsen Ismail; Mona Monir Kamel (Cairo : Mohamed Tawfik Mohamed Nemr, 2016)
This thesis comprises four chapters. The first chapter is an introduction which includes the solid phase synthesis and biological activity of benzimidazoles, quinoxalines and isoalloxazines. The second chapter clarifies the objectives of the work and schemes designed for the preparation of the target compounds. The third chapter deals with the theoretical discussion of the experimental work, molecular docking and results of cytotoxic activity. The fourth chapter includes the experimental part of the thesis which contains the detailed procedures used for the synthesis of the target compounds and intermediates, in addition to their physical properties, their elemental analyses and spectral data. Moreover, it includes the docking steps of all compounds. The in vitro cytotoxic activity of the synthesized compounds on breast cancer cell line (MCF-7), human hepatic cell line (HEPG2) and human colorectal cell line (HCT116) compared with doxorubicin as a reference anticancer agent is also included in this chapter
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Organic Chemistry
Issued also as CD
Keywords: Benzimidazoles; Quinoxalines; Solid phase synthesis